2003
DOI: 10.1016/s0006-3495(03)74792-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Roles of HIV-1 gp41 Pretransmembrane Sequence Segmentation

Abstract: The membrane-proximal segment connecting the helical core with the transmembrane anchor of human immunodeficiency virus type 1 gp41 is accessible to broadly neutralizing antibodies and plays a crucial role in fusion activity. New predictive approaches including computation of interfacial affinity and the corresponding hydrophobic moments suggest that this region is functionally segmented into two consecutive subdomains: one amphipathic at the N-terminal side and one fully interfacial at the C-terminus. The N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
102
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 58 publications
8
102
0
Order By: Relevance
“…However, the functional HIV-1 envelope spike is a putative trimer in which the MPER of one gp41 may be close to the MPER on a neighboring gp41. Moreover, MPER peptides have been shown to self-interact or oligomerize on membranes (1,30,55). We hypothesize that these substitutions weaken a specific interaction between the MPERs of neighboring gp41s.…”
Section: Discussionmentioning
confidence: 94%
“…However, the functional HIV-1 envelope spike is a putative trimer in which the MPER of one gp41 may be close to the MPER on a neighboring gp41. Moreover, MPER peptides have been shown to self-interact or oligomerize on membranes (1,30,55). We hypothesize that these substitutions weaken a specific interaction between the MPERs of neighboring gp41s.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, MPER peptide structures in solution have been defined to be random by CD spectroscopic analysis (21). However, more defined secondary structures have been described for some shorter peptides (D 664 -K 683 ) both in solution and in micelle-or liposomebound states in infrared (17,26,30) and CD spectroscopic studies (16). More recently, nuclear magnetic resonance spectroscopic studies of micelle-bound peptides corresponding to E 662 -K 683 (31) and S 649 -K 683 (8) revealed that the C-terminal half of MPER consists of two shorter helices separated by a short hinge and that the N-terminal half of MPER is mostly disordered.…”
Section: Resultsmentioning
confidence: 99%
“…The dye transfer assay reinforced the notion that the pre-TM region participates in formation and expansion of fusion pores (46). Biophysical studies showed that the abilities of peptides derived from residues 664 to 683 to adopt a helical structure and form homo-oligomers in solution and membranes correlate with their abilities to induce vesicle fusion and inhibit gp41-induced cell-cell fusion (58,64). This sequence is thought to specifically interact with cholesterol-containing membranes, since cholesterol and sphingomyelin in liposomes promote pre-TM peptide surface self-aggregation and destabilization of the membrane architecture (59).…”
Section: Discussionmentioning
confidence: 99%